Electric Vehicle Charging Business Models: A Comparative Analysis of Delhi and London - Kurien, Joseph Mathew (2022)
There is widespread interest in improving Electric Vehicle (EV) adoption globally in recognition that it will have a positive impact on the environment and on attaining sustainability. Although EV adoption is improving, the EV market still competes with gasoline cars and faces barriers like lack of charging infrastructure, and limited EV range.